2011
DOI: 10.1002/hbm.21368
|View full text |Cite
|
Sign up to set email alerts
|

Response inhibition and reward anticipation in medication‐naïve adults with attention‐deficit/hyperactivity disorder: A within‐subject case‐control neuroimaging study

Abstract: Results underline the implication of the reward system in ADHD adult pathophysiology and suggest that frontal abnormalities during response inhibition performance may not be such a pivotal aspect of the phenotype in adulthood. In addition, our findings point toward response variability as a core feature of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 76 publications
7
62
0
3
Order By: Relevance
“…RT variability can be regarded as a measure of performance consistency, and might reflect fluctuations in attention during executive control tasks (Stuss, Murphy, Binns, & Alexander, 2003). Although this result is modest, it is consistent with previous findings that have linked both increased reward sensitivity and RT variability to ADHD (Adams et al, 2011;Carmona et al, 2012;Mitchell & Nelson-Gray, 2006), and indirectly supports the proposal of wider RT variability as an endophenotype for ADHD (Castellanos et al, 2005;van Rooij et al, 2015), which predisposes individuals to poor impulse control and other deficits. The association that links RT variability, omission errors and reward sensitivity suggests that high-SR individuals display less consistent performance, which might be detrimental in some executive tasks.…”
Section: Reward Sensitivity and Behavior In The Go/no-go Tasksupporting
confidence: 89%
See 1 more Smart Citation
“…RT variability can be regarded as a measure of performance consistency, and might reflect fluctuations in attention during executive control tasks (Stuss, Murphy, Binns, & Alexander, 2003). Although this result is modest, it is consistent with previous findings that have linked both increased reward sensitivity and RT variability to ADHD (Adams et al, 2011;Carmona et al, 2012;Mitchell & Nelson-Gray, 2006), and indirectly supports the proposal of wider RT variability as an endophenotype for ADHD (Castellanos et al, 2005;van Rooij et al, 2015), which predisposes individuals to poor impulse control and other deficits. The association that links RT variability, omission errors and reward sensitivity suggests that high-SR individuals display less consistent performance, which might be detrimental in some executive tasks.…”
Section: Reward Sensitivity and Behavior In The Go/no-go Tasksupporting
confidence: 89%
“…However, the behavioral pattern of ADHD patients in response inhibition tasks is not only characterized by long stopping latencies, but also by poorer performance in the main (go) task, manifested as longer reaction times (RTs), more errors and increased RT variability (Bellgrove et al, 2005;Braet et al, 2011;Carmona et al, 2012;Karalunas et al, 2012;Sebastian et al, 2012;van Rooij et al, 2015;Vaurio et al, 2009). Wide RT variability is one of the most robust findings for the performance of ADHD patients during response inhibition tasks (Alderson et al, 2007), and has been proposed as an endophenotype for this disorder (Castellanos et al, 2005;van Rooij et al, 2015).…”
mentioning
confidence: 99%
“…At a population level, individuals with ADHD display deficits in several neurocognitive domains such as working memory, inhibitory control, vigilance, and planning (94,95). This leads to suboptimal decision making and preference for immediate as opposed to delayed rewards (96,97).…”
Section: Etiologymentioning
confidence: 99%
“…An RDoC approach could probably identify several domains shared by ADHD, SUD and possibly at least some forms of binge eating. Earlier studies have identified several different mechanisms involving reward deficiency, difficulties in emotional regulation, lack of inhibitory control, and preference for immediate versus later rewards present in ADHD (94)(95)(96)(97). These could potentially contribute to the overlap with SUDs (73) and also with binge eating (93).…”
Section: Future Considerationsmentioning
confidence: 99%
“…fMRI studies showed a hypofunctioning in ADHD of VS to cues predicting future rewards (Carmona, et al, 2011;Hoogman, et al, 2011;Scheres, Milham, Knutson, & Castellanos, 2007;Strohle, et al, 2008). Furthermore, in ADHD, OFC activation is altered during the delivery of signalled rewards (Strohle, et al, 2008) and during reinforcement in attentional tasks (Cubillo, Halari, Smith, Taylor, & Rubia, 2011).…”
Section: Rl Impairment In Adhdmentioning
confidence: 99%